2007
DOI: 10.1093/jxb/erl265
|View full text |Cite
|
Sign up to set email alerts
|

Differential feedback regulation of ethylene biosynthesis in pulp and peel tissues of banana fruit

Abstract: The feedback regulation of ethylene biosynthesis in banana [Musa sp. (AAA group, Cavendish subgroup) cv. Grand Nain] fruit was investigated in an attempt to clarify the opposite effect of 1-methylcyclopropene (1-MCP), an ethylene action inhibitor, before and after the onset of ripening. 1-MCP pre-treatment completely prevented the ripening-induced effect of propylene in pre-climacteric banana fruit, whereas treatment after the onset of ripening stimulated ethylene production. In pre-climacteric fruit, higher c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 36 publications
5
61
0
3
Order By: Relevance
“…Ten days after harvest, ethylene production of all fruits (with or without AVG spraying) was not significant different. This result is quite appropriate with results previously reported by Innaba [Innaba et al, 2007] respectively.…”
Section: Effect Of Avg Spraying Time On Ethylene Production Of Bananasupporting
confidence: 93%
“…Ten days after harvest, ethylene production of all fruits (with or without AVG spraying) was not significant different. This result is quite appropriate with results previously reported by Innaba [Innaba et al, 2007] respectively.…”
Section: Effect Of Avg Spraying Time On Ethylene Production Of Bananasupporting
confidence: 93%
“…However, Trivellini et al (2011) have shown that ethylene biosynthesis can be under both positive and negative feedback regulatory mechanisms in a tissue-temporal-specific manner during flower development and senescence depending on differential expression of ACS and ACO genes. Similarly, the studies in tomato and banana have shown a differential feedback regulation of ethylene biosynthesis enzymes between pre-climacteric and ripening fruits and also between different tissues (Nakatsuka et al 1998;Inaba et al 2007). …”
Section: Generative Phase Of Developmentmentioning
confidence: 92%
“…A positive feedback regulation, through an increase in ethylene production triggered by exogenous ethylene, with the activation of ACS and/or ACO has been reported for petunia (Tang and Woodson 1996), carnation (Jones and Woodson 1997), and orchid (O'Neill et al 1993). A negative feedback regulation has been shown for transgenic petunia flowers (Wilkinson et al 1997) and ripening tomato and banana (Nakatsuka et al 1998;Inaba et al 2007). However, Trivellini et al (2011) have shown that ethylene biosynthesis can be under both positive and negative feedback regulatory mechanisms in a tissue-temporal-specific manner during flower development and senescence depending on differential expression of ACS and ACO genes.…”
Section: Generative Phase Of Developmentmentioning
confidence: 95%
“…Indeed, the change in phenolic content in immature green fruit unable to respond to ethylene might be under the control of developmental cues while in mature green fruit both ethylene and developmental cues might be involved. Recent progress on the ripening process in banana strongly suggests that the ripening process of banana peel tissue clearly differs from that of the pulp (Domínguez and Vendrell, 1994;Clendennen and May, 1997;Inaba et al, 2007), thus suggesting tissuespecific regulation of the ripening process in this species. Independent of climactic season and fruit physiological stage at harvest, phenol content accumulates differentially in peel tissue compared to pulp tissue during ripening.…”
Section: Fig 3 Modification Of Enthalpy Limits For the Wp And Dpmentioning
confidence: 99%